Bexmarilimab-induced macrophage activation leads to treatment benefit in solid tumors : The phase I/II first-in-human MATINS trial - Rannikko Jenna H.; Verlingue Loic; de Miguel Maria; Pasanen Annika; Robbrecht Debbie; Skytta Tanja; Iivanainen Sanna; Shetty Shishir; Ma Yuk Ting; Graham Donna M.; Arora Sukeshi Patel; Jaakkola Panu; et al. (Cell Press, 2025)
Summary Macrophage Clever-1 contributes to impaired antigen presentation and suppression of anti-tumor immunity. This first-in-human trial investigates the safety and tolerability of Clever-1 blockade with bexmarilimab in patients with treatment-refractory solid tumors and assesses preliminary anti-tumor efficacy, pharmacodynamics, and immunologic correlates. Bexmarilimab shows no dose-limiting toxicities in part I (n = 30) and no additional safety signals in part II (n = 108). Disease control (DC) rates of 25%–40% are observed in cutaneous melanoma, gastric, hepatocellular, estrogen receptor-positive breast, and biliary tract cancers. DC associates with improved survival in a landmark analysis and correlates with high pre-treatment intratumoral Clever-1 positivity and increasing on-treatment serum interferon γ (IFNγ) levels. Spatial transcriptomics profiling of DC and non-DC tumors demonstrates bexmarilimab-induced macrophage activation and stimulation of IFNγ and T cell receptor signaling selectively in DC patients. These data suggest that bexmarilimab therapy is well tolerated and show that macrophage targeting can promote immune activation and tumor control in late-stage cancer.